Facile activation of Si-H bond by an electrophilic carbene - Swamy, V. S. V. S. N.; Kundu, Gargi; Sen, Sakya S. (Indian Chemical Society, 2018)
Herein, we have explored the chemistry of 1,3-bis(2,6-di-isopropylphenyl)-5,5-dimethy1-4,6-diketopyrimidinyl-2-ylidene (1) with various silanes under mild conditions. The oxidative addition of Si-H bond of phenylsilane with DAC 1 affords the compound 2, which is unambiguously characterized by muitinuclear NMR spectroscopy, elemental analysis, and X-ray single crystal diffraction studies. Interestingly, DAC 1 activates silicon hydride bond of chlorosilanes at room temperature and results in the corresponding silylation products.

Saturated N-heterocyclic carbene based thiele's hydrocarbon with a tetrafluorophenylene linker - Kundu, Gargi; De, Sriman; Tothadi, Srinu; Das, Abhishek; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2019)
The synthesis of a SIPr [1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] derived Kekule diradicaloid with a tetrafluorophenylene spacer (3) has been described. Two synthetic routes have been reported to access 3. The cleavage of C-F bond of C6F6 by SIPr in the presence of BF3 led to double C-F activated compound with two tetrafluoro borate counter anions (2), which upon reduction by lithium metal afforded 3. Alternatively, 3 can be directly accessed in one step by reacting SIPr with C6F6 in presence of Mg metal. Compounds 2 and 3 were well characterized spectroscopically and by single-crystal X-ray diffraction studies. Experimental and computational studies support the cumulenic closed-shell singlet state of 3 with a singlet-triplet energy gap (Delta ES-T) of 23.7 kcal mol(-1).
Keywords: C-F activation; Density functional calculations; fluorine; Kekule diradicaloids; saturated NHC

Cyanosilylation by compounds with main-group elements: an odyssey - Pahar, Sanjukta; Kundu, Gargi; Sen, Sakya S. (ACS Omega, 2020)
The past few decades have seen remarkable headways in the structural and reaction chemistry of compounds with heavier main-group elements. In recent years, there is an ongoing effort to derive catalytic chemistry involving main-group compounds, driven by their lower costs and higher terrestrial abundances. Here, a survey on the state-of-the-art in the development of cyanosilylation methodology by compounds with heavier main-group elements has been given. Once dominated by transition metals, the field has matured to embrace the majority of the main-group elements including aluminum, silicon, and calcium. Of particular focus will be how the mechanism of cyanosilylation involving compounds with main-group elements differs from those of transition metals.

Stepwise nucleophilic substitution to access saturated N-heterocyclic carbene haloboranes with boron-methyl bonds - Kundu, Gargi; Pahar, Sanjukta; Tothadi, Srinu; Sen, Sakya S. (Organometallics, 2020)
Compounds of boranes with N-heterocyclic carbenes are known, yet little attention has been paid to NHC compounds of boron bearing methyl and halogen moieties together. The reason can be attributed to the hazardous methyldichloroborane (MeBCl2), which ignites in air. We describe here convenient solution-phase access to SIDipp.MeBCl2 (SIDipp = 1,3-bis(2,6-diisopropylphenyl)imidazolin-2-ylidene) (3) by a salt metathesis reaction of SIDipp.BCl3 (2) with MeLi. Replacement of the chlorine atoms of 3 with stepwise addition of AgOTf led to the formation of SIDipp.MeBCl(OTf) (4) and SIDipp.MeB(OTf)2 (5). In the case of 4, all of the substituents on the boron atom are different. Subsequently, we extended our synthetic approach to the amidinate system and prepared PhC(NtBu)2B(Me)Cl (7) from the reaction of PhC(NtBu)2BCl2 (6) with MeLi.

Diverse reactivity of carbenes and silylenes towards fluoropyridines - Kundu, Gargi; Ajithkumar, V. S.; Bisai, Milan Kumar; Tothadi, Srinu; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
The reaction of IDipp with C5F5N led to functionalization of all three carbon atoms of the imidazole ring with HF2- as the counter-anion (1). Reactivity with 2,3,5,6-tetrafluoropyridine gives only C-F bond activation leaving C-H bonds intact (5b). The reaction of SIDipp with C5F5N in the presence of BF3 afforded the ring cleavage product (3). Analogous reactions with silylene led to oxidative addition at the Si(II) center.

Nucleophilic substitution at a coordinatively saturated five-membered NHC center dot haloborane centre - Kundu, Gargi; Tothadi, Srinu; Sen, Sakya S. (Inorganics, 2022)
In this paper, we have used a saturated five-membered N-Heterocyclic carbene (5SIDipp = 1,3-bis-(2,6-diisopropylphenyl)imidazolin-2-ylidine) for the synthesis of SNHC-haloboranes adducts and their further nucleophilic substitutions to put unusual functional groups at the central boron atom. The reaction of 5-SIDipp with RBCl2 yields Lewis-base adducts, 5-SIDipp center dot RBCl2 [R = H (1), Ph (2)]. The hydrolysis of 1 gives the NHC stabilized boric acid, 5-SIDipp center dot B(OH)(3) (3), selectively. Replacement of chlorine atoms from 1 and 2 with one equivalent of AgOTf led to the formation of 5-SIDipp center dot HBCl(OTf) (4) and 5-SIDipp center dot PhBCl(OTf) (5a), where all the substituents on the boron atoms are different. The addition of two equivalents of AgNO3 to 2 leads to the formation of rare di-nitro substituted 5-SIDipp center dot BPh(NO3)(2) (6). Further, the reaction of 5-SIDipp with B(C6F5)(3) in tetrahydrofuran and diethyl ether shows a frustrated Lewis pair type small molecule activated products, 7 and 8.
Keywords: NHC-haloboranes; nucleophilic substitution; saturated NHC; tetra-coordinate boron

Six-membered saturated NHC-stabilized borenium cations: isolation of a cationic analogue of borinic acid - Kundu, Gargi; Balayan, Kajal; Tothadi, Srinu; Sen, Sakya S. (Inorganic Chemistry, 2022)
The reaction of six-membered saturated NHC [1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene; henceforth abbreviated as 6-SIDipp] with PhBCl2 yields a Lewis base adduct, 6-SIDipp.PhBCl2 (1), which readily undergoes nucleophilic substitution reaction with AgNO3, leading to the single (2) and double (3) substitution of both chlorides with ONO2 moieties at the boron atom. The reaction of 1 with 1 equiv of AlCl3 resulted in a borenium cation of composition [6-SIDipp.B(Ph)Cl]+ (4) with AlCl4- as the counteranion. Although borenium cations with different substituents on boron have been reported, a structurally characterized phenylchloroborenium cation remains unknown. Similarly, the reaction of 1 with triflic acid provides the first representative of a new class of borenium cations bearing one hydroxyl and one phenyl group on boron (5), a cationic analogue of borinic acid. Ph-BN H Diphenylborinic acid

Substitution at sp(3) boron of a six-membered NHC center dot BH3: convenient access to a dihydroxyborenium cation - Kundu, Gargi; Ajithkumar, V. S.; Raj, K. Vipin; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we have undertaken the synthesis and investigated the reactivity of a 6-membered saturated NHC borane adduct (1). Direct electrophilic halogenation of 1 with a stoichiometric amount of I-2 led to NHC boryl iodides, 6-SIDipp center dot BH2I (2) and 6-SIDipp center dot BHI2 (3), which were further reacted with various nucleophiles to give novel 6-SIDipp based mono and disubstituted boranes with OTf (4 and 6) or ONO2 (5 and 7) functional groups. The addition of Br-2/H2O to 1 smoothly results in a dihydroxyborenium cation (8).

Versatile chemistry of six-membered NHC with boranes: bromination at sp(3) borane, activation of the B-H bond of HBpin, and ring expansion of NHC - Kundu, Gargi; Dixit, Ruchi; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Dalton Transactions, 2022)
The NHC.borane chemistry has been majorly restricted to imidazol-2-ylidene classes of carbenes. In our previous communication, we reported the synthesis of 6-SIDipp center dot BH3 [6-SIDipp = 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene] and its electrophilic substitution reaction with iodine. Here, we have shown selective bromination of a 6-SIDipp stabilized sp(3) B-H bond. Treatment of 1.2 equivalents of N-bromosuccinamide with 6-SIDipp center dot BH3 gives a mixture of mono- and disubstituted products 6-SIDipp center dot BH2Br (1) and 6-SIDipp center dot BHBr2 (2). However, the reactions with alkyl bromides or carbon tetrabromide resulted in 6-SIDipp center dot BH2Br (1) selectively. Exploration of the chemistry of 6-SIDipp with BHCl2 and 9-BBN (9-borabicyclo[3.3.1]nonane) led to mono-6-SIDipp adducts 3 and 6a. Furthermore, 6a undergoes ring expansion to afford a seven-membered product, 6b, under mild conditions. Unlike BHCl2 or 9-BBN, the B-H bond of HBpin undergoes oxidative addition upon reaction with 6-SIDipp, epitomizing the first example (7) of a B-H bond insertion at NHCs. The analogous reactivity with HBcat led to a tetra-hydropyrimidinium salt with B(cat)(2) as a counteranion (8).

Enhancing diradical character of chichibabin's hydrocarbon through fluoride substitution - Kundu, Gargi; Dash, Soumya Ranjan; Kumar, Ravi; Vanka, Kumar; Ghosh, Aryya; Sen, Sakya S. (ChemPlusChem, 2023)
In this work, 5-SIDipp [SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] (1) derived Chichibabin's hydrocarbon with an octafluorobiphenylene spacer (3) has been reported. The addition of two equivalents of 5-SIDipp with decafluorobiphenyl in presence of BF3 gives the double C-F bond activated imidazolium salt with two tetrafluoroborate anions, 2. Further reduction of 2 gives the fluorine substituted 5-SIDipp based Chichibabin's hydrocarbon, 3. Quantum chemical calculations suggested a singlet state of 3 with a singlet-triplet energy gap (?ES-T) of 3.7 kcal mol(-1), which is substantially lower with respect to the hydrogen substituted NHC-based Chichibabin's hydrocarbons (10.7 kcal mol(-1), B3LYP). As a result, the diradical character (y) of 3 (y=0.62) is also noticeably higher than the hydrogen substituted CHs (y=0.41-0.43). The ?ES-T was found to be higher in CASSCF (22.24 kcal mol(-1)) and CASPT2 (11.17 kcal mol(-1)) for 3 and the diradical character (d) is 44.6 %.
Keywords: C-F Bond Activation; Chichibabin & PRIME; DFT; N-Heterocyclic carbene; s Hydrocarbon

Six-membered NHC stabilized monomeric zinc complexes - Gour, Kritika; Kundu, Gargi; Dash, Soumya Ranjan; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2023)
This paper describes the rare use of a 6-membered saturated N-heterocyclic carbene (NHC) known as 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene (abbreviated as 6-SI-Dipp) as a ligand in zinc chemistry. We report on the investigation of the reactions between 6-SI-Dipp and ZnX2, which resulted in a range of new monomeric 6-SIDipp center dot ZnX2 complexes (X=Et (1), Cl (2), Br (3), and I (4)). We also prepared a new NHC zinc complex where the two substituents of the zinc atom are different, 6-SIDipp center dot Zn(Et)Br (7) through the reaction of the proligand [6-SIDippH]Br with ZnEt2. We have observed that the reactions of complex 1 with sulfur and HBpin led to the removal of the ZnEt2 moiety, resulting in the formation of a C=S double bond and a B H activation product, respectively. Lastly, the reaction of 1 with five-membered NHCs led to the exchange of carbene and the formation of either 5-IDipp center dot ZnEt2 (8) or 5-SIDipp center dot ZnEt2 (9).
Keywords: Lewis adduct; NHC; X-ray diffraction; zinc

Taming the parent oxoborane - Kundu, Gargi; Amrutha, P. R.; Raj, K. Vipin; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Chemical Science, 2023)
Despite recent advancements in the chemistry of multiply bound boron compounds, the laboratory isolation of the parent oxoborane moiety, HBO has long remained an unsolved and well-recognized challenge. The reaction of 6-SIDipp(.)BH3 [6-SIDipp = 1,3-di(2,6-diisopropylphenyl)tetrahydropyrimidine2-ylidene] with GaCl3 afforded an unusual boron-gallium 3c-2e compound (1). The addition of water to 1 resulted in the release of H-2 and the formation of a rare acid stabilized neutral parent oxoborane, LB(H)]O (2). Crystallographic and density functional theory (DFT) analyses support the presence of a terminal B=O double bond. Subsequent addition of another equivalent of water molecule led to hydrolysis of the B-H bond to the B-OH bond, but the `B=O' moiety remained intact, resulting in the formation of the hydroxy oxoborane compound (3), which can be classified as a monomeric form of metaboric acid.

Access to NHC-Boryl mono- and bis-selenide and utility as mild selenium transfer reagent including to the C-F bond - Kundu, Gargi; Amrutha, P. R.; Tothadi, Srinu; Sen, Sakya S. (Chemistry- a european journal, 2024)
Reactions of 5-SIDipp & sdot; BH3 (5-SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene) (1) with diphenyldiselenide provide access to 5-SIDipp-boryl mono- (5-SIDipp & sdot; BH2SePh) (2) and bis-selenide (5-SIDipp & sdot; BH(SePh)2) (3). The facile cleavage of the B-Se bond makes 2 a neutral source of selenium nucleophiles in substitutions reactions with benzyl bromides, and provide access to the corresponding selenoethers. The direct transformations of one of the C(sp2)-F bonds of C5F5N and C6F5CF3 to C-Se bonds have also been achieved by the use of 2 without employing transition-metal catalysts. While it was previously established that C6F6 could undergo complete defluoroselenation under harsh conditions, we successfully achieved partial defluorination of C6F6 by employing 2 as a mild selenide transfer reagent. During the formation of C-Se bonds through the cleavage of C-F bonds, the potential by-product NHC & sdot; BH2F undergoes ring expansion of the NHC, leading to the formation of the six-membered diaazafluoroborinane (7). Access to NHC & sdot; boryl mono- and bis-selenides from NHC & sdot; BH3 has been achieved. The boryl mono selenide has been demonstrated to function as a selenium transfer reagent, enabling the synthesis of selenoethers from benzyl bromide. Additionally, it can also facilitate the conversion of the challenging aromatic C-F bond to a C-Se bond, resulting in concomitant ring expansion of NHC & sdot; haloborane.image
Keywords: boron; C-F Bond Activation; N-Heterocyclic carbene; Ring expansion; Selenium

Saturated NHC-stabilized borenium, boronium, hydride-bridged boron cations, and a bora-acyl chloride - Kundu, Gargi; Amrutha, P. R.; Tothadi, Srinu; Sen, Sakya S. (ORGANOMETALLICS, 2024)
Keywords: activation; BORINIUM; Chemistry

Unprecedented C-F bond cleavage in perfluoronaphthalene during cobaltocene reduction - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Sangole, Mayur; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Singh, Kirandeep; Sen, Sakya S. (DALTON TRANSACTIONS, 2024)

Development of six-membered saturated cyclic diaminocarbenes in main-group chemistry - Kundu, Gargi; Sen, Sakya S. (Dalton Transactions, 2025)
In recent years, there has been a remarkable surge in the utilization of saturated N-heterocyclic carbenes (NHCs) as ligands in main group chemistry. While the field has predominantly focused on five-membered NHCs and cyclic alkyl(amino) carbene (CAAC) ligands, the investigation of six-membered NHCs (6-NHCs) has only just begun. Despite possessing higher nucleophilicity than their five-membered counterparts, 6-NHCs have been less explored due to their lack of structural rigidity. This feature article aims to highlight recent developments in 6-NHCs in only main group chemistry. Exciting new studies have demonstrated the activation of B-H bonds in HBpin, ring expansion from a six-membered to a seven-membered ring under ambient conditions, and the stabilization of transient units ``H-B 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 O'' and ``(OH)BO'', among other intriguing phenomena. A major focus of this review is on synthetic approaches for 6-NHC-stabilized main-group compounds and their unusual properties, as revealed by spectroscopic and crystallographic data. While the chemistry of 6-NHCs is still in its nascent stage, the findings presented in this feature article underscore the need for its exploration and further investigation. Furthermore, this review provides valuable insights into effective synthetic methods for creating new 6-NHCmain group (B, Al, Si, P, Zn, etc.) complexes, along with mechanistic explanations for some of these reactions. These advances hold great promise for the future development of this exciting and rapidly evolving field of N-heterocyclic carbene chemistry.

Kekule diradicaloid with a naphthalene spacer - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2026)
The availability of a diverse array of carbenes led to the generation of a catalog of carbene based Kekule diradicaloids, but the linker in such molecules is mostly limited to phenylene or biphenylene. Here we have prepared a closed-shell Kekule diradicaloid (2) separated by a naphthalene moiety and stabilized by two capping 5-SIDipp [5-SIDipp = 1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] from the reduction of the corresponding dication (1). The combined experimental and computational studies confirm that 2 is in a closed-shell singlet state exhibiting a singlet-triplet energy difference (Delta ES-T) of 18.7 kcal/mol, which is considerably lower than Thiele's version (29.1 kcal/mol).